Current practice in project appraisal in Europe - Odgaard, Thomas; Kelly, Charlotte; Laird, James (Proceedings from the Annual Transport Conference at Aalborg University, 2005)
Trans European Network transport infrastructure projects and regulations pose a significant problem in the area of appraisal. Whereas previously national appraisal guidelines have been used for the appraisal of such projects there is an increased demand for consistency of approach where projects cross country boundaries or have some other international dimension. With the EU expanding to 25 countries in 2004 this has become an even more pertinent issue. The purpose of the 6th framework HEATCO project (from which this paper is derived) is to develop a set of harmonised guidelines for project assessment and transport costing at an EU level. This paper will present the approaches, methods and values currently used for project appraisal and then review their comparability and consistency across the 25 member states. It is the first general attempt to include the current appraisal practice of the 10 new member states in a review. The review is based on the results from a country based proforma, which was designed to elicit the extent to which the different elements of infrastructure appraisal are harmonised and highlight what potential barriers to harmonisation may exist. In doing this it builds on the previous survey undertaken as part of the EUNET project (Grant-Muller, Mackie, Nellthorp and Pearman, 1998), updating it to account for the changes in practice that have occurred over the intervening 7 years as well as extending it to the new member states. The elements of infrastructure appraisal practice that will be reviewed are: appraisal methodology and framework; construction related costs including the treatment of uncertainty and optimism bias; user benefits and vehicle operating costs; safety; environmental impacts and indirect socio-economic effects. The analysis and comparison of existing practice of project assessment and transport costing highlights a number of similarities and differences across countries and modes. For example, all countries use cost benefit analysis in some form, but for countries in the east region of the EU (e.g. Latvia) cost benefit analysis is most commonly/ only used for projects which are promoted for EU co-funding. There are also clear regional differences on how to treat the different impacts of a project, such as noise effects. None of the countries in the south region of the EU (Cyprus, Greece, Italy, Malta, Portugal or Spain) include noise in a cost benefit analysis. The review shows that while some points of commonality exist between EU countries there is still a long way to go to achieve harmonisation in national practices. It concludes with a discussion of some of the key issues that need to be resolved before the harmonisation of guidelines for project assessment and transport costing at the EU level can be achieved.